QTL Mapping of the Shape of Type VI Glandular Trichomes in Tomato - Bennewitz, Stefan; Bergau, Nick; Tissier, Alain (Frontiers in Plant Science, 2018)
Glandular trichomes contribute to the high resistance of wild tomato species against insect pests not only thanks to the metabolites they produce but also because of morphological and developmental features which support the high production of these defense compounds. In Solanum habrochaites, type VI trichomes have a distinct spherical shape and a large intercellular storage cavity where metabolites can accumulate and are released upon breaking off of the glandular cells. In contrast, the type VI trichomes of S. lycopersicum have a four-leaf clover shape corresponding to the four glandular cells and a small internal cavity with limited capacity for storage of compounds. To better characterize the genetic factors underlying these trichome morphological differences we created a back-cross population of 116 individuals between S. habrochaites LA1777 and S. lycopersicum var. cerasiformae WVa106. A trichome score that reflects the shape of the type VI trichomes allowing the quantification of this trait was designed. The scores were distributed normally across the population, which was mapped with a total of 192 markers. This resulted in the identification of 6 QTLs on chromosomes I, VII, VII and XI. The QTL on chromosome I with the highest LOD score was confirmed and narrowed down to a 500 gene interval in an advanced population derived from one of the back-cross lines. Our results provide the foundation for the genetic dissection of type VI trichome morphology and the introgression of these trichome traits into cultivated tomato lines for increased insect resistance.